2019
DOI: 10.1029/2019ja026946
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Particle Drift Resonance Dynamics Near Poloidal Mode Field Line Resonance Structures

Abstract: We examine the effect on drift‐resonant particle dynamics of a strongly peaked internally driven poloidal mode field line resonance (FLR; with specified frequency ω in the Pc5 range and azimuthal mode number m≫1). Using an analytic magneto‐hydrodynamic model in a dipole field to describe the ultra low frequency wave mode, we use the bounce‐averaged formalism of Northrop (1963) to obtain equations of motion for charged particles in the wave frame and find an analytic solution for the case of a temporally consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
(103 reference statements)
2
17
0
Order By: Relevance
“…Recent electron PSD compilations measured from both the Relativistic Electron‐Proton Telescope (REPT; Baker, Kanekal, Hoxie, Batiste, et al, ) and the MagEIS instruments on board the Van Allen Probes can be found, for instance, in Zhao et al () and Boyd et al (). Analytic solutions are possible only in simple configuration; for example, Degeling et al () in this collection calculate analytically ULF wave fields and drifting electron fluxes near a poloidal mode field line resonance in a dipole field.…”
Section: Particle Acceleration and Transport In The Inner And Outer Zmentioning
confidence: 99%
“…Recent electron PSD compilations measured from both the Relativistic Electron‐Proton Telescope (REPT; Baker, Kanekal, Hoxie, Batiste, et al, ) and the MagEIS instruments on board the Van Allen Probes can be found, for instance, in Zhao et al () and Boyd et al (). Analytic solutions are possible only in simple configuration; for example, Degeling et al () in this collection calculate analytically ULF wave fields and drifting electron fluxes near a poloidal mode field line resonance in a dipole field.…”
Section: Particle Acceleration and Transport In The Inner And Outer Zmentioning
confidence: 99%
“…These ULF waves, especially their poloidal-mode branches with electric field oscillations in the azimuthal direction, can accelerate or decelerate charged particles as they follow magnetic gradient and/or curvature drift orbits around Earth. In other words, this process provides an important energy source for particle acceleration and transportation in the Van Allen radiation belts Liu et al, 2016;Mann et al, 2016;Sarris et al, 2017;Hao et al, 2019;Degeling et al, 2019). This resonant process is called drift resonance (Southwood and Kivelson, 1981;Southwood and Kivelson, 1982;, during which particles can have a net energy gain (or loss, depending on the phase difference) from the ULF waves.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reverse-boomerang stripes on electron pitch angle distributions can be observed by Van Allen channels. [Li et al, 2018] A nonlinear theory of drift resonance has been developed to formulate the charged particle motion due to the ULF wave of a large amplitude [Li et al, 2018, 2020, Degeling et al, 2019. Observable signatures such as rolled-up structures in the energy spectrum are predicted.…”
Section: Ulf Waves' Interaction With Ionospheric Outflow: Mass Spectrometermentioning
confidence: 99%
“…In the traditional drift or drift-bounce resonance theory, the weak ULF wave-particle interaction is assumed and charged particle trajectories are unperturbed, thus, a linearization theory can be applied. However, the observed ULF waves in the magnetosphere are usually with a larger magnitude, therefore, the traditional theory needs to be extended into a nonlinear regime since charged particle trajectories are strongly disturbed [Li et al, 2018, Degeling et al, 2019. In this section, the concepts on the nonlinear and multiple drift/drift-bounce resonances will be presented.…”
Section: Nonlinear and Multiple Drift/drift -Bounce Resonancesmentioning
confidence: 99%
See 1 more Smart Citation